HIV/AIDS, agriculture and food security in Malawi: Background to action - Ngwira, Naomi; Bota, Sam; Loevinsohn, Michael E. (International Food Policy Research Institute, 2001)
It is now widely accepted that AIDS in not just a health issue. In the recently developed Poverty Reduction Strategy Paper, the Malawi people and government designated HIV/AIDS as a crosscutting issue, and the Malawi National HIV/AIDS Strategic Framework 2000-2004 calls for “an expanded, multi-sectoral national response to the epidemic.” However the capacity to respond to these calls lags behind. In many sectors, policy making still proceeds as if HIV/AIDS never happened.